Analysis of Cooperative Management in Improving Member Welfare in Civil Servant Cooperatives - Harlina Legi; Amonto Sari Nilla (STIE Amkop Makassar, 2023)
A Cooperative is a business entity that is a legal entity and is based on kinship by prioritizing a sense of brotherhood for all members. Cooperatives are present in society to advance the welfare of members and society in general. This study aims to provide an understanding of cooperative management in improving the welfare of members. The research conducted is descriptive qualitative research. The approach used is a management, juridical and normative approach. Informants in this study: cooperative managers, secretaries, treasurers, employees, and members at KPN Kandou Hospital Manado. The results of the research show that cooperatives have various business units. These cooperatives play an active role in improving the welfare of their members in the savings and loan unit program offered by KPN RSUP Kandou Manado. However, there are obstacles, such as the need for more awareness of the borrower in a cooperative business unit and the absence of collateral in providing credit loans.